Integrated global assessment of the natural forest carbon potential - Mo, Lidong; Zohner, Constantin M; Reich, Peter B; Liang, Jingjing; de Miguel, Sergio; Nabuurs, Gert-Jan; Renner, Susanne S; van den Hoogen, Johan; Araza, Arnan; Herold, Martin; Mirzagholi, Leila; Ma, Haozhi; et al. (Nature, 2023)
Forests are a substantial terrestrial carbon sink, but anthropogenic changes in land use and climate have considerably reduced the scale of this system1. Remote-sensing estimates to quantify carbon losses from global forests2-5 are characterized by considerable uncertainty and we lack a comprehensive ground-sourced evaluation to benchmark these estimates. Here we combine several ground-sourced6 and satellite-derived approaches2,7,8 to evaluate the scale of the global forest carbon potential outside agricultural and urban lands. Despite regional variation, the predictions demonstrated remarkable consistency at a global scale, with only a 12% difference between the ground-sourced and satellite-derived estimates. At present, global forest carbon storage is markedly under the natural potential, with a total deficit of 226 Gt (model range = 151-363 Gt) in areas with low human footprint. Most (61%, 139 Gt C) of this potential is in areas with existing forests, in which ecosystem protection can allow forests to recover to maturity. The remaining 39% (87 Gt C) of potential lies in regions in which forests have been removed or fragmented. Although forests cannot be a substitute for emissions reductions, our results support the idea2,3,9 that the conservation, restoration and sustainable management of diverse forests offer valuable contributions to meeting global climate and biodiversity targets.
Keywords: zachování přírodních zdrojů; trvale udržitelný rozvoj; sekvestrace uhlíku; Forests; Sustainable Development; Global Warming; biodiverzita; lidské činnosti; Carbon Sequestration; Environmental Restoration and Remediation; globální oteplování; Carbon; uhlík; Conservation of Natural Resources; Human Activities; regenerace a remediace životního prostředí; Biodiversity; lesy